Age bias in the criteria for antisocial personality disorder. (May 2021) - Holzer, Katherine J.; Vaughn, Michael G.; Fearn, Noelle E.; Loux, Travis M.; Mancini, Michael A.
Abstract: The prevalence of antisocial personality disorder (ASPD) decreases with age. As such, research regarding ASPD typically focuses on children and younger adults. The apparent age-specific prevalence of ASPD may be due, in part, to diagnostic criteria informed by research excluding older adults. The present study sought to better understand the manifestation of ASPD in older adults and investigate potential age bias in the diagnostic criteria. Item response theory methods were used to the diagnostic criteria for ASPD with data from the National Epidemiologic Survey on Alcohol and Related Conditions Wave III. The measurement of three ASPD criteria showed uniform differential item functioning (DIF), suggesting that older adults were less likely to endorse the item than younger adults despite having the same level of underlying personality disorder. The items with DIF are related to the following criteria for ASPD: Failure to conform to social norms with respect to lawful behaviors as indicated by repeatedly performing acts that are grounds for arrest (3 items with DIF); irritability and aggressiveness, as indicated by repeated physical fights or assaults (1 item with DIF); and consistent irresponsibility, as indicated by repeated failure to sustain consistent work behavior or honor financial obligations (1 item with DIF). Results of the present study can be used to inform the development of criteria that better capture the age-specific experience of this disorder. Improved criteria will result in increased diagnostic accuracy, systematic estimation of the prevalence, improved assessments, and more effective treatment options for this complex population.